2019
DOI: 10.3389/fphar.2019.00961
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antiviral Components of Ma Huang Tang and Investigation on the Ephedra Alkaloids Efficacy on Influenza Virus Type A

Abstract: Although Ma Huang Tang (MHT) has long been considered as a classical formula for respiratory infections like influenza, bronchitis and asthma, its chemical ingredients that really exert the main efficacy are still obscure. In this study we aimed to screen its antiviral components and investigate the potential mechanisms. The MDCK cellular research results showed that, among nine predominant ingredients of MHT, L-methylephedrin (LMEP), L-ephedrine (LEP) and D-pseudo- ephedrine (DPEP) significantly inhibited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…And luteolin was also resistant to dengue virus, influenza A virus, Japanese encephalitis virus, and so on [ 50 52 ]. In addition, ephedrine alkaloids, such as ephedrine, pseudoephedrine, and methylephedrine, had potential therapeutic effects on viral-induced respiratory infections [ 53 ]. This indicated that ephedra-bitter almond may resist COVID-19 through antiviral and sympathomimetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…And luteolin was also resistant to dengue virus, influenza A virus, Japanese encephalitis virus, and so on [ 50 52 ]. In addition, ephedrine alkaloids, such as ephedrine, pseudoephedrine, and methylephedrine, had potential therapeutic effects on viral-induced respiratory infections [ 53 ]. This indicated that ephedra-bitter almond may resist COVID-19 through antiviral and sympathomimetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), the first identified member of TLR family, is a transmembrane protein characterized by an extracellular domain containing leucine-rich repeats (LRRs) with which the MD-2 molecule is associated [52]. After activated by virus, the TIR domain of TLR4 interacts with the TIR domain of MyD88 and binds to another TIR-containing adaptor protein, MyD88 adaptor-like (MAL), leading to an inflammatory cascade effector enzyme such as the expression of TNF-α, IL-1β, and IL-6 [53][54][55][56]. Thus, when B4 bound to TLR4, it will prevent the virus from activating TLR4, which may be an alternative strategy to treat FM1-induced viral pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), the rst identi ed member of TLR family, is a transmembrane protein characterized by an extracellular domain containing leucine-rich repeats (LRRs) with which the MD-2 molecule is associated [53]. After activated by virus, the TIR domain of TLR4 interacts with the TIR domain of MyD88 and binds to another TIR-containing adaptor protein, MyD88 adaptor-like (MAL), leading to an in ammatory cascade effector enzyme such as the expression of TNF-α, IL-1β, and IL-6 [54][55][56][57]. Thus, when B4 bound to TLR4, it will prevent the virus from activating TLR4, which may be an alternative strategy to treat FM1-induced viral pneumonia.…”
Section: Discussionmentioning
confidence: 99%